Development and stability evaluation of a facial cleanser formulation containing pomegranate extract (Punica granatum L.) (Research, Society and Development, 2022)
The present study aimed to develop and evaluate the stability of a facial liquid cleanser prepared with different pomegranate peel extracts (Punica granatum L.). For this, pomegranate peel extracts were prepared by two forms of solid-liquid extraction, soxhlet and maceration. Then, liquid cleanser formulations were developed containing 5% of the extracts obtained, which were subsequently subjected to a stability study, for a predefined period of 60 days, stored at room temperature (25.0 ± 3.0 ºC), under refrigeration (5.0 ± 3.0 ºC) and in a dryer oven (40.0 ± 3.0 ºC). Physicochemical analyses, such as evaluation of organoleptic characteristics (odor, color and general aspect), pH determination and centrifugation test, were performed at times t0, t7, t15, t30 and t60 days after formulation. Changes in color, pH and viscosity of the formulations subjected to heat were observed, with emphasis on the formulation prepared with the soxhlet extract stored in the oven (SE), while the formulations stored at room temperature remained stable. Based on the results, it is concluded that the formulations at room temperature of both extracts remained stable during the period of 60 days, when stored at an average of 25ºC ± 3ºC. Comparing the formulations, the formulation containing extract obtained by maceration showed greater stability in terms of viscosity and color characteristics. Therefore, further studies need to be carried out to evaluate the differences between the composition of extracts and impacts on stability, in addition to investigating the effectiveness of the formulation.